The Mechanisms for Implementing Tax Control and Their Effectiveness in Reducing Tax Evasion According to Algerian Tax Legislation: A Case Study of an Institution in Algeria - Bouakaz, Youcef (The Journal of Accounting and Management, 2025)
This study aims to evaluate the effectiveness of tax control in reducing tax evasion among businesses, through a case study of a company that was found guilty of tax evasion and fined according to Algerian tax legislation. The study adopted a descriptive-analytical approach, using data collection and analysis to examine the impact of regulatory measures on tax compliance. The results showed that tax control measures play a significant role in reducing instances of tax evasion and increasing compliance with financial laws, particularly when fines and penalties are applied. The study also recommends updating tax control tools and adopting modern techniques to enhance the efficiency of tax collection. Additionally, it suggests strengthening cooperation between the relevant authorities to ensure a transparent and sustainable economic environment. This research highlights the importance of continuously improving tax enforcement mechanisms to achieve higher levels of compliance and contribute to economic stability. It also emphasizes the need for a dynamic approach to tackling tax evasion, focusing on both preventative measures and effective penalties. The findings of this study provide valuable insights for policymakers and tax administrators in Algeria and similar contexts.